A macro-micro analysis of gender segregation and job quality in Latin America - Diksha Arora; Elissa Braunstein; Stephanie Seguino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Latin America has seen vast improvements in gender educational and health equality. Favourable supply-side conditions, however, have not translated into greater gender economic equality, a process that also depends on structural economic change and global macroeconomic conditions. In this paper, we assess the role of a variety of macro-level policies and structures in influencing trends in women's access to high-quality jobs for a sample of 15 countries in Latin America over the period 1990-2018. Using micro-level data, we first evaluate women's relative share of good jobs, defined as women's weekly earnings in an industry or occupation relative to the median wage. Further, we econometrically estimate the impact of a variety of macro-level variables on the relative quality of women's jobs. Results indicate that the most significant and robust positive predictor of women's relative access to good jobs is public social spending as a share of GDP. Other important macro-covariates include measures of labour market policy, monetary and fiscal policy, and macroeconomic structure and global orientation, including financial openness. The results suggest that macro-level structures and policies related to globalization that hamper the achievement of greater gender equality can be offset by appropriately targeted government policies.
Keywords: J31; N36; E50; O54; 330; gender economic equality; Latin America; macroeconomic structure; structural economic change